Improving Student Behavior and School Discipline with Family and Community Involvement - Sheldon, Steven B.; Epstein, Joyce L. (Education and urban society, 2002)
This study reports the results of efforts of school officials to implement family and community involvement activities to reduce the number of disciplinary actions and to ensure a school climate focused on learning. Using longitudinal data from elementary and secondary schools, analyses indicate that regardless of schools’prior rates of discipline, the more family and community involvement activities were implemented, the fewer students were disciplined by being sent to principals’offices or given detention or in-school suspension. Activities for two types of involvement, parenting and volunteering, were most predictive of reducing the percentages of students who were subject to discipline. Also, schools that improved the quality of their partnership programs reported fewer students in need of discipline. The results suggest that creating more connections and greater cooperation among the school, family, and community contexts may be one way for schools to improve student behavior and school discipline.